Analisa Inovasi Online Shop By Wiast Store Official - Widy Astuti; Syam Gunawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Nowadays, more and more young students have their own businesses. They are supported by technological advances and the ease of obtaining information... There have been many students who have successfully run their businesses well. Entrepreneurship is something that really needs to be done by the Indonesian people today, entrepreneurship can be a solution to the problem of unemployment in our country.